Priority 5: Mediterranean food consumption patterns: diet, environment, society, economy and health - Lacirignola C.; Capone R.; El Bilali H.; Debs P.; Cardone G.L.; Driouech N.; Dernini S.; Burlingame B.; Gitz V.; Meybeck A. (Feeding knowledge, 2017)
The objective of this White paper is to highlight the role that the current food consumption patterns play in food and nutrition security, public health, environment protection and socio-economic development in the Mediterranean region. The ultimate aim is to stimulate a multidisciplinary dialogue among the Euro-Mediterranean scientific community on the sustainability of current food consumption and production patterns in the Mediterranean region and beyond, to identify the research activities and policy actions needed to move towards more sustainable Mediterranean food systems.
Expo Milano 2015